انقرائية النصوص في العلوم المعرفية: مفاهيم وقياسات - صيام، كريمة (المدرسة العليا للأساتذة الشيخ مبارك الميلي بوزريعة, 2024)
نحاول من خلال هذه الدراسة تسليط الضوء على مفهوم الانقرائية في النصوص مهما كان نوعها، قصد تحديد المصطلح من الناحية اللغوية والمعرفية، كما نقدم أهم العوامل المؤثرة في الانقرائية، إلى جانب أساليب قياسها في النصوص حسب الأدبيات السابقة التي تناولت بالدراسة درجة صعوبة النصوص، وذلك بهدف الإجابة عن الأسئلة الآتية: -ما مفهوم الانقرائية في ضوء العلوم المعرفية؟ ما العوامل المؤثرة فيها؟ وما أساليب قياسها؟. ومن أهم النتائج التي توصلت إليها الدراسة: -ليس هناك تعريف جامع شامل لمفهوم انقرائية النصوص، وأغلب الباحثين في هذا المجال يحصرون معنى الانقرائية في الوضوح وسهولة قراءة النصوص وإدراك معناها، ومدى مناسبتها للفئة العمرية التي أعدت من أجلها، -هناك أساليب ومقاييس عدة لدراسة الانقرائية، فبعضها اهتم بالنص فقط وبعضها الآخر تناول القارئ أو القارئ والمقروء معا.، -أكثر مقاييس انقرائية النصوص شيوعا هو اختبار كلوز (Cloze) لموضوعيته وسهولة بنائه وتطبيقه. Through this study, we try to shed light on the problem of the concept of readability in texts of any kind, in order to define the term from a linguistic and cognitive point of view. It also presents the most important factors affecting readability, as well as methods for measuring text readability according to previous principals that dealt with the study of the degree of difficulty of texts, with the aim of answering the following questions: What is the concept of readability in the light of cognitive science? What are the factors affecting it? What are the methods of measuring it?. One of the most important findings of the study is that there is no comprehensive definition of the concept of texts readability, and most researchers in this field limit the meaning of readability to clarity, ease of reading texts and understanding their meaning, and their suitability for the age group for which they were prepared. On the other hand, the study showed that there are several methods and measures for the readability study, some of which are concerned with the text only, while others deal with the reader or the reader and the read together. The current study found that the most common measure of text readability is the cloze test, for its objectivity and ease of construction and application.
Keywords: مفهوم "الانقرائية" -- العلوم المعرفية -- النصوص القرائية